The development of an assesment framework for vocational education taining programmes in the noss based training system (NBTS) and the national dual training system (NDTS) - Muhammad Zain, Ruminah (2016)
There are two skills training systems in Malaysia, namely NOSS Based Training System (NBTS) and National Dual Training System (NDTS). Although both systems have different training and assessment approaches, both systems produce national skilled workers with the same certification known as the Malaysian Skills Certificate (MSC). In order to manage and monitor both systems concurrently, a standardised assessment system need to be in place to ensure that the training given is efficient and effective in producing competent and employable k-workers. Therefore, the objective of the study was to develop a comprehensive assessment framework for both skill training systems as guidance to those personnel who are involved in conducting skill training. This study used mixed method mode approach and utilised structured interview, questionnaire and mapping table from document analysis as data collection instruments to gather information on the dimension of assessment. The sample of the study constituted 269 personnel from accredited centers and agencies which conduct NDTS or/and NBTS approaches. Several statistical techniques were used to analyse the data: descriptive statistics (frequency, mean, standard deviation and percentage) was used to explain the respondents profile; Exploratory Factor Analysis (EFA) was used to determine the dimension of the assessment framework and this was validated by Parallel Analysis (PA) and the Minimum Average Partial (MAP) test; descriptive from the EFA was used to develop a model of assessment framework and this model was validated by the use of Structural Equation Modeling (SEM). There were three outcomes from the study. Firstly, both systems NBTS and NDTS were considered similar although some of the sub dimensions were not. From this finding, a common assessment framework was developed for NBTS and NDTS approaches with special treatment for the differences. Secondly, six dimensions of assessment framework were identified, and finally an assessment framework for both systems was developed. The developed assessment framework will ensure whether the quality of assessment in the accredited center achieves the international skill standard.